Examination Of The Relationship Between The Identification Levels And Aggression Levels Of The Fans; Example Of Alanyaspor Fans - Yasemin Karademir; Hasanali Kağan Kurnaz (Selcuk University, 2020)
ABSTRACT The primary objective of this study is to examine the relationship between the levels of identification of fans with their teams and their levels of aggression. In addition, it is aimed in this study to determine whether the levels of identification and aggression of fans differ according to their personal information. Alanyaspor fans (n=305) were the participants of the study. In the study, the "Sports Fan Identification Scale", developed by Wann and Branscombe in 1993 and determined by Günay and Tiryaki in 2003 to be suitable for Turkish sports fans and the "Buss and Perry Aggression Scale", developed by Buss and Perry in 1992 and demonstrated by Madran in 2012 to be suitable with its Turkish form, were used. The normality distribution of the data was examined with the Kolmogorov-Smirnov test and as a result, it was evaluated with correlation analysis, t test and one-way variance analysis (Anova) in the analysis of inter-parameters relations. At the end of the study, it was found that there was no relationship between the identification levels of the fans and their general levels of aggression, but there was a significant relationship between their levels of identification and their levels of physical aggression. However, it was seen that there was a positive-significant relationship between the level of identification of the fans and age, gender, marital status, the state of going to a home match and the state of going to an away match, that there was a negative-significant relationship between the level of identification of the fans and the level of education and the membership of the fans group. Finally, it was observed that there was a negative-significant relationship between the aggression levels of the fans and the age, marital status and the state of going to a home match, while there was a positive-significant relationship between the aggression levels of the fans and their educational status. Key words: Fan, Identification, Aggression